Gelechiidae of the Canary Islands (Spain). Part 1. Anacampsinae (Insecta: Lepidoptera) - Per Falck; Ole Karsholt (SHILAP, 2025)
The Gelechiidae subfamily Anacampsinae in the Canary Islands is revised. We recognize 20 species and one subspecies of Anacampsini and three species of Chelariini. Seven species and two subspecies are described as new: Stomopteryx palmella Falck & Karsholt, sp. nov. (Spain: La Palma), Stomopteryx cuestaella Falck & Karsholt, sp. nov. (Spain: Gran Canaria and Tenerife), Stomopteryx minimella Falck & Karsholt, sp. nov. (Spain: Gran Canaria), Stomopteryx variabilis Falck & Karsholt, sp. nov. (Spain: Gran Canaria, Tenerife, La Gomera, La Palma and El Hierro), Aproaerema ayacatella Falck & Karsholt, sp. nov. (Spain: Gran Canaria), Aproaerema pseudomercedella Falck & Karsholt, sp. nov. (Spain: La Gomera and El Hierro), Aproaerema angustumella Falck & Karsholt, sp. nov. (Spain: Tenerife and La Palma), Stomopteryx schizogynae grancanariella Falck & Karsholt, ssp. nov. (Spain: Gran Canaria) and Nothris congressariella tenerifensis Falck & Karsholt, ssp. nov. (Spain: Tenerife). The status of Gelechia elachistella (Stainton, 1859) is changed into a synonym of the nominotypical subspecies of Aproaerema anthyllidella (Hübner, [1813]), stat. nov. The use of subspecies in the Gelechiidae is discussed. Mesophleps silacella (Hübner, 1796), Mesophleps ochracella (Turati, 1926) and Anarsia lineatella Zeller, 1839 are recorded as new to the Canary Islands. We also present several records of species new to single Canary Islands. The paper is illustrated with photographs of adults and genitalia of the new species as well as of other species when relevant. Analyses of DNA barcodes show that the identifications and distinctiveness of each species as well-supported and genetically isolated.